2020
DOI: 10.1037/pspp0000218
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of knowing and liking with accuracy and positivity bias in person perception.

Abstract: A great range of person perception phenomena may be conceptualized in terms of how much perceivers know about the targets, how much they like the targets and how these factors relate to the extent to which target descriptions reflect actual target characteristics and/or evaluative bias. We present a comprehensive empirical analysis of this interplay in two studies, the second (targets: N = 189, informants: N = 1352) being a pre-registered replication of the first (targets: N = 73, informants: N = 549). Using m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 88 publications
(176 reference statements)
5
70
1
Order By: Relevance
“…Some evidence for this was uncovered in previous studies (e.g. Wessels, Zimmermann, Biesanz, & Leising, 2020). Such an effect seems possible for various reasons: for example, perceivers who like their targets may be aware of their targets' more negative characteristics but simply not report them out of loyalty.…”
Section: Longitudinal Predictions Using Different Data Sourcesmentioning
confidence: 78%
See 1 more Smart Citation
“…Some evidence for this was uncovered in previous studies (e.g. Wessels, Zimmermann, Biesanz, & Leising, 2020). Such an effect seems possible for various reasons: for example, perceivers who like their targets may be aware of their targets' more negative characteristics but simply not report them out of loyalty.…”
Section: Longitudinal Predictions Using Different Data Sourcesmentioning
confidence: 78%
“…The present study uses unique longitudinal data on psychologically meaningful life experiences, which have not been published before. They are part of a larger dataset with Wave 2 personality ratings previously utilized as part of Study 2 in Wessels et al (2020). Before consenting to participate, participants were fully informed about purpose and procedures of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The core finding from previous research motivating the present study is that the "social desirability" value of person-descriptive terms (Edwards, 1953(Edwards, , 1957 closely mirrors the extent to which the use of those terms reflects the perceivers' self-reported attitudes toward their targets (Leising et al, 2014(Leising et al, , 2016Wessels et al, 2020). For example, the profile correlation between a perceiver's descriptions of a target on several items and the social desirability values of those items correlates almost perfectly with how much the perceiver says he or she likes the target (r ¼ .92; Leising et al, 2015).…”
mentioning
confidence: 63%
“…Edwards (1953Edwards ( , 1957 showed that the items on which perceivers describe targets in personality research may be very reliably judged in terms of their "social desirability", that is, the extent to which using them to describe a person casts a more positive, neutral, or negative light on that person. Later research showed that such ratings also align very closely with the extent to which the actual usage of an item may be predicted from the attitude that the perceiver reports having toward the target (Leising et al, 2013;Wessels et al, 2020).…”
mentioning
confidence: 79%
“…First, we dropped the Study 1 analyses from the manuscript entirely because the results did not significantly differ NETWORK APPROACH TO REPUTATIONS from those from the replication analyses in Study 2, making them less precise but otherwise redundant with integrated analyses on the combined Study 1 and Study 2 data (which were part of Study 2's preregistration). Second, we incorporated the extended SAM analyses (Biesanz, 2010;Wessels et al, 2020). The extended SAM affords greater power and parsimonious tests of consensus, accuracy, and positivity bias that are integrated across items and personality domains.…”
Section: Methods Preregistrationmentioning
confidence: 99%